Exact traveling wave solutions to the higher-order nonlinear Schrodinger equation having Kerr nonlinearity form using two strategic integrations. - Nestor, Savaissou; Betchewe, Gambo; İnç, Mustafa; Doka, Serge Y. (Springer Heidelberg, 2020)
In this paper, exact traveling wave solutions to the higher-order nonlinear Schrodinger equation having Kerr nonlinearity form are derived, by adopting two relevant architecture of integration methods namely the extended sinh-Gordon equation expansion method and extended Jacobi elliptic function methods (EJEF method). The studied model, describes the propagation of optical solitons in nonlinear optical fibers. As a results, various types of traveling wave solutions are obtained including Jacobi elliptic function solutions. For some special cases, when the modulus of m approach 0 or 1 it is gained respectively periodic wave solutions and hyperbolic function solutions. Comparing our results with the well-known results in literature are also reported. Lastly the 3D profile to some of the obtained solutions are also plotted.
Keywords: Elliptic Function-Method; Soliton-Solutions; Gordon; Bright